Features of formation of productivity of sweet sorghum hybrids depending on the influence of agrotechnical factors: width of row spacing, crop density and processing by growth regulator - Л. І. Сторожик; О. В. Музика (Plant Varieties Studying and Protection)
Purpose. Identify the peculiarities of the growth and development of plants, formation of productivity of sweet sorghum hybrids for different widths of row spacing, crops density and the use of the growth stimulant Vympel 2 in the zone of the Forest-Steppe Ukraine. Methods. The study used hybrids ‘Dovista’ and ‘Huliver’. The width of the row spacing was 45 and 70 cm for the density of the crops: 150 thousand pcs/ha, 200 thousand pcs/ha, 250 thousand pcs/ha. Sorghum seed treatment was carried out using Vympel 2 (0.5 l/t) growth stimulant and its additional foliar application in the tillering stage of the crop (0.5 l/ha). Results. Studies have revealed that the ‘Dovista’ hybrid has a significant potential for productivity due to a longer growing season. At different widths of row spacing and density of plants standing, the hybrid ‘Dovista’ yield exceeded the average by 3.6 t/ha of‘Huliver’ hybrid. The yield increase at the level of 7.3–13.0 t/ha was obtained in the variant of application of growth stimulant Vympel 2 at 45 cm of row spacing and changes in sowing rates from 150 to 250 thousand pcs/ha. Similar variants of experiment at 70 cm of width of row spacing ensured collection of vegetative mass of sweet sorghum at 6.7–12.6 t/ha more than in control variants. The growth stimulant Vympel 2 increased the accumulation of dry matter in ‘Dovista’ hybrid with a row spacing of 45 cm and various seeding rates by 1.3–4.3 t/ha, whereas with a row spacing of 70 cm – by 1.2–3.5 t/ha. In the ‘Huliver’ hybrid in similar experiments, an increase in dry matter was obtained at the level of 1.7–3.9 t/ha, and the application of the growth regulator ensured the collection of dry matter of sweet sorghum by 1.3–3.0 t/ha above the control variants. Total sugar content in the variants of the experiment was biased. Application of seed treatment with growth stimulant Vympel 2 (0.5 l/t) followed by foliar application in the tillering stage (0.5 l/ha) increased the content of total sugars by 0.15, but this slight deviation was within the experimental margin. Conclusions. The highest yield of green mass at a density of 250 thousand plants per hectare and seed treatment with growth stimulant Vympel 2 (0.5 l/t) + foliar application in the tillering stage (0.5 l/ha) provided the ‘Dovista’ hybrid – 98.8 t/ha, which is 5.3 t/ha more than in the ‘Huliver’ hybrid for the width of the row spacing of 45 cm. In the phase of physiological maturity of the grain, the content of total sugars in sweet sorghum was, on average, at the level of 15.0%, in the ‘Dovista’ hybrid – 15.4%, in the ‘Huliver’ hybrid – 14.7%.